Development of wireless RTD temperature measurement using decade box - Olivea, Karen Buhan (2010)
The project proposed is to develop GUI (Graphical User Interface) application using visual basic. Wireless system is interfacing between camputer-based and instrument for temperature measurement to measure temperature where the data from measurement process can be directly use for other purpose, such as calculation and data monitoring. This project will involve designing the GUI application to monitor temperature changes using visual basic 2008. Manual method in temperature measurement are measure and calculate the data manually. The system is developed to facilitate for taking the data directly from the computer. This project will use the wireless RTD system as a sensor to interface between computer and temperature instrument such as temperature transmitter. Wireless RTD system that will use is called Zig-bee technology. Zig-bee technology are self configuring short range network and low cost. Decade box will use as a testing and calibration to create a resistance or capacitance with a specific value by using a combination of the rotary decade switches. For this project, the expected outcome is GUI application will monitor temperature changes through Zigbee wireless system. This project will make the wireless process instrumentation and wireless terminal technology for instrumentation directly leads to efficient process and equipment validation in current technology.